Beyond the Screen: Transformasi Pembelajaran Anak Usia Dini Melalui Virtual Reality - Sonia, Della Rizki (Jurnal Informatika & Teknologi Cerdas, 2025)
In a time of swift technological progress, traditional learning methods are transitioning to more engaging and interactive digital formats. The early years of life represent a vital phase in human growth, which makes the selection of effective teaching strategies essential for fostering lasting learning achievements. This research seeks to investigate the application of Virtual Reality (VR) technology as a pedagogical resource to boost digital skills and involvement among preschool-aged children. The approach taken comprises a review of existing literature paired with initial observations utilizing a basic 3D VR educational game model. Preliminary findings suggest that the incorporation of VR can enhance children's concentration, creativity, and involvement in their educational experience. The research concludes that Virtual Reality has the potential to serve as a groundbreaking option for reshaping early childhood education, particularly in the presentation of visual and hands-on learning resources. This research supports the progress toward Sustainable Development Goals (SDGs) 4 and 9.